Análisis Estratigráfico Secuencial de las Formaciones Huincul y Lisandro del Subgrupo Río Limay (Grupo Neuquén - Cretácico Tardío) en el Departamento El Cuy, Río Negro, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the Cuy Department, Rio Negro Province (Fig. 1), there are outcrops of the Late Cretaceous continental deposits of the Subgroup Rio Limay (Fig. 2), in virtually continuous exposures that allow detail studies and exploration of the architecture of the sedimentary bodies. This contribution presents the results of the sedimentological study and sequential stratigraphic analysis for the depositional period of the Huincul and Lisandro formations (Subgroup Río Limay). The outcrops appear in the Planicie de Rentaría (Area A), with continuous sections longer than 3 km and Anfiteatro (Area B) with outcrops of more than 5 km (Fig. 1). In these areas we made detailed sedimentological profiles (Fig. 3), we described and interpreted lithofacies and architectural elements employing photograms and we defined stratigraphically significant discontinuities. We identified 11 fluvial lithofacies, 4 conglomerates (Gm, Gh, Gp and Gt), 5 sandstones (Sm, St., Sp, and Mr. Sh), and 2 pelitic (Fl and Fm), according to the nomenclature of Miall (1996). In addition, 2 volcaniclastic lithofacies, 1 primary pyroclastic lithofacies (Tlpm) and 1 volcaniclastic sineruptive lithofacies (TLpe) following criteria Mc Phie et al. (1993) were defined, and finally 3 eolic lithofacies (Spe, She and Sathya) (Fig. 4). These were grouped into 11 fluvial architectural elements and 4 eolic (Fig. 5). We have recognized channel elements (CHI) and CHII), intrachannel (LA, DAI, DAII, SBI and SBII) and floodplain (CRI, CRII, CS and OF). The eolic architectural elements include dunes (ED) and interdunes (DI, and WI FI).The paleoenvironments sedimentary include river systems, terminal fans and dune fields. The Sistema Fluvial I (SF-I) is integrated by LA, DAI, DAII, SBI, CHI, CRI, CRII and OF (Fig. 6). The meanders loops show, in most cases, complete filling sequences in which records of migration of large sand dunes are preserved which retain topsets deposits and the scrolls their undulating tops. The channel belts are separated by potent floodplain deposits, with frequent intercalation of levels of overflow both channelized or in mantle, and show a multilateral persistence in potent sections of the column. The crevasse splay exhibits paleosoils with low levels of development, frequent presence of gleyzed horizons and high degree of bioturbation. The general characteristics of the S-FI are proper of aggrading fluvial systems of high sinuosity. The Sistema Fluvial II (SF-II) is characterized by LA, DAI, DAII, SBI and to a lesser proportion, by CRI and OF (Fig. 6). The meanders loops often show preservation of the channel fill by lateral accretion with complete successions. Also the dunes preserve topsets deposits and the scrolls the original topography (Fig. 7). The frequency of conservation of filling phase of the abandoned channel with strong bioturbation and development gleyzed horizons suggests frequent avulsion by strangulation. The preservation of the floodplain is low, and it is characterized by intense bioturbation, and a high volcaniclastic participation in some reaches. We consider that the fluvial system model is of high sinuosity highly aggrading. The terminal fan system (Sistema Abanico Terminal) (TSS), characteristic of semiarid regions with strong seasonal climatology, is represented by CHII, CS or SBII and OF (Fig. 6). These constitute flooding basin deposits (CI), simple multiepisodic channel fillings corresponding to middle sections of the distributary plain and simple channels with development of small transversal cross bars and multilateral relations of distal distributary plain. The aeolian system (Sistema Eolico) (IS) consists of SD, DI, WD and FD. The spatial distribution of dunes and interdunes, the high dispersion of paleocurrents with a principal mode at the avalanche deposits and multiple stabilization surfaces suggest the development of a field of barchan dunes. In the element WI, we identified ferric and mottled halos and bioturbations that indicate the presence of paleosoils with gleyzed horizons (Retallack, 1976, 1990) which and characterize environments with good oxygenation.According to the temporal and spatial arrangement of the different paleoenvironments, their evolutionary trend and the analysis of significant discontinuity surfaces, we produced the stratigraphic sequence for the Subgroup Rio Limay (Fig. 8). The sequence starts with the Secuencia I, corresponding to the base of the Huincul Fm and is represented by SF-I, defined by belts of potent channels, isolated in floodplain deposits and with the development of overflow fans under conditions of rapid aggradation. The avulsion by overflow crevasse splay was the control mechanism of the system. The development of composite paleosoils in distal segments of the plain indicates the existence of long periods during which the channel band remained relatively stable positions. The incorporation of volcaniclastic materials to fluvial deposits claims a volcanic activity close in time. The geometry and continuity of the sandy bodies and its proportion in relation to the floodplain deposits suggests periods of low frequency of avulsion/subsidence rate. The large-scale architecture observed is the equivalent to a High Accommodation System Track (Cortejo) (AA) with a ratio A/S close to 1 associated with a gradual decline in the base level under conditions of high sediment supply. A net surface (Discontinuidad D-IS-IS) is the basis of the sequence II, marked by an abrupt change in the fluvial architecture river (SF-II). The mechanism of lateral migration was by strangulation and abrupt cut of the bends. Only underdeveloped paleosoils in the abandoned channel fillings and the little preservation of the floodplain deposits are recognized. The stacking of channel belts signs out a reduction in the accommodation space. The top layer of Huincul Fm is interpreted as Lower Accommodation System Track (Cortejo) (BA). The Discontinuity IIC (D-IIC) marks the base of Lisandro Fm, which is an surface of fluvial flooding defining the expansion of a terminal fan system associated with an abrupt increase in the accommodation space and rapid progradation of the facies of an environment of intermediate distributary plain. This stretch of the Sequence is interpreted as the High Accommodation System Track (Cortejo) (AA) of the Sequence II (S-II) was associated with a period of high subsidence. The deposits of terminal fans are covered by a wet eolian system (IS). The change in the depositional environment marks the beginning of the Sequence III (SIII), limited at the base by D-IIIS. The development of a field of parabolic dunes associated with environments dry, wet and flooded interdune indicates a gradual rise in the water table that, eventually, was above the depositional surface generating shallow lagoons. The short-term climatic changes related with an increase in precipitation and the relative position of the water table controlled the development stabilization surfaces and the growth and migration of aeolian forms. We identified two supersurfaces (D-IV and DV, Fig. 18) which may be assigned to periods with an increase in the supply or availability of sediment climatically conditioned. Periodically, the interdune corridors were overrun by ephemeral streams associated with the flood basin environments of SAT during flooding events. All deposits, characterized by a strong stacking of the eolian successions are interpreted as the Cortejo BA from the Sequence III. A new fluvial flood event marked by the Discontinuity VIC, is represented by facies flood basin, a distributary plain with the development of intertwined channels showing evidence of the SAT progradation. This sector is interpreted as the (Cortejo) AA System Track of S-III associated with a period of renewed subsidence. D-VIIS limits the base of the S-IV whose (Cortejo) BA System Track is similar to the previous Sequence and includes 3 supersurfaces (D-D-VIIIIX / X). The expansion of the flooding basin facies of a limited terminal fan at the base by D-XIC represents the base of the (Cortejo) AA System Track of the Sequence IV. Tabular units associated with a distal distributary plain that replaced towards the top by thick channels of low sinuosity close to the backbone of the system represent an progradation event of the SAT. The beginning of the Sequence V is marked D-XIIS associated with the development of a new SE. The architectural design of large scale is similar to that of the (Cortejos) BA System Tracks of the Sequences III and IV and includes supersurfaces D-D-XIII and XIV. Something similar occurs with the surface of fluvial flooding (D-XVC) on which we identified a prograding succession of SAT. The characteristics of the systems involved in the Lisandro Fm suggest a climate change to semi-arid conditions and low gradient in the depositional environment.The sequential stratigraphic analysis of the formations Huincul and Lisandro suggests that the deposits are sinorogénic and the different pulses of subsidence are registered in the (Cortejos) AA and BA System Tracks defined in this study.
Keywords: Stratigraphy Sequence; Sedimentology; Río Limay Sugroup; Neuquén Group; Río Negro